Predictive value of topoisomerase IIα immunostaining in urothelial bladder carcinoma. Issue 4 (1st April 2001) - Nakopoulou, L; Zervas, A; Lazaris, A Ch; Constantinides, C; Stravodimos, C; Davaris, P; Dimopoulos, C
Abstract : Aims —The nuclear enzyme DNA topoisomerase II has been shown to be required for chromatin condensation and chromosomal segregation during mitosis; its isoform topo IIα is linked with active cell proliferation in mammalian cells. The aim of this study was to examine the relation of the expression of topo IIα to the biological behaviour of conventional urinary bladder cancer. Methods —Formalin fixed, paraffin wax embedded tissue from 94 specimens of bladder urothelial cancer were immunohistochemically stained for topo IIα. For each case, a topo IIα index was determined. A similar index had been determined for Ki-67, a known cell proliferation marker. Each case had also been graded, staged, and evaluated for DNA ploidy as well as for p53 and bcl-2 immunoreactivity. Results —Raised topo IIα expression (in ≥ 10% of malignant nuclei) correlated with two adverse prognosticators—high grade (p = 0.027) and invasion of the muscularis propria (p = 0.013), but with no other evaluated parameter. By multivariate survival analysis using Cox's proportional hazard model, high expression of topo IIα was found to be predictive for worse survival (p = 0.0047). Patients' age, tumour stage, and grade were also retained as independent prognostic factors (p = 0.0349, p = 0.00005, and p = 0.0130, respectively). The negative influence of increased topo IIα immunopositivity on patients' survival was also seen in the subgroup of patients with non-muscle invasive carcinomas (p = 0.0004), in patients with a bcl-2 negative phenotype (p = 0.0330), and in those with low Ki-67 indices (p = 0.0341). Conclusions —Because topo IIα and Ki-67 failed to demonstrate a significant inter-relation, they appear to be different molecules that both function at separate phases in the complex process of cellular proliferation. The assessment of increased topo IIα immunoreactivity in specimens from urothelial carcinomas might help to select patients (particularly among those with superficial tumours) in the worse prognostic categories for new therapeutic strategies.